2020
DOI: 10.1175/ei-d-19-0029.1
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Occurrence of Water Deficit in Soybean Cultivated in Lowland Soils

Abstract: The occurrence of water deficit is intensified in lowland soils. Generating information regarding its risk of occurrence is essential to avoid seed yield losses. The objective of this study was to determine the probability of water deficit in soybean cultivated in lowlands of the Vacacaí and Piratini river basins in the southern portion of Rio Grande do Sul as a function of the sowing date. Soybean development was simulated considering three sets of cultivars of relative maturity groups (RMG) delimited by 5.9-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In particular, the high temperatures and the missing precipitation in June 2017 affected soybean growth in a critical phase before flowering. Bortoluzzi et al (2020), Grassini et al (2015), and Karam et al (2005) have shown that drought stress can significantly reduce soybean grain yield. Cover crop treatments resulted in decreased soybean grain yield, filled pods plant −1 , pod density, grain density, LAI, and plant height for kidney vetch and ryegrass and for grain yield pod −1 after corn cockle in 2016 and in 2017.…”
Section: Soybean Yield Components Plant Growth and Weather Conditionsmentioning
confidence: 99%
“…In particular, the high temperatures and the missing precipitation in June 2017 affected soybean growth in a critical phase before flowering. Bortoluzzi et al (2020), Grassini et al (2015), and Karam et al (2005) have shown that drought stress can significantly reduce soybean grain yield. Cover crop treatments resulted in decreased soybean grain yield, filled pods plant −1 , pod density, grain density, LAI, and plant height for kidney vetch and ryegrass and for grain yield pod −1 after corn cockle in 2016 and in 2017.…”
Section: Soybean Yield Components Plant Growth and Weather Conditionsmentioning
confidence: 99%
“…Soybean is mainly grown in tropical, subtropical, and temperate regions ( FAO, 2021 ). It is very sensitive to water scarcity and suffers greatly in terms of growth and development under water deficit conditions ( Bortoluzzi et al., 2020 ). Consequently, global warming and changes in precipitation patterns pose a significant threat to soybean production, especially in areas lacking of rainwater or irrigation ( Cotrim et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…These lowland soils are limited by the natural drainage process because coupled with the relief that is unfavorable to surface runoff, the low atmospheric demand for water vapor, and the more abundant autumn/winter rainfall, cause waterlogging to become more frequent and prolonged (Bortoluzzi, Heldwein, Trentin, Maldaner, & Silva, 2020;Goulart, Reichert, & Rodrigues, 2020). Soil waterlogging compromises gas exchange in the root system, primarily oxygen and CO 2 (Ploschuk, Miralles, Colmer, Ploschuk, & Striker, 2020).…”
Section: Introductionmentioning
confidence: 99%